Вплив мінеральних добрив на врожайність гороху озимого та ярого в Степу України - Губарєв, Ілля Дмитрович; Hubariev, Illia (ЦНТУ, 2025)
В даній випускній кваліфікаційній роботі вивчали вплив двох кратних доз амофосу при використанні його в якості припосівного удобрення при вирощуванні чотирьох сортів ярого (Саламанка, Мадонна) та озимого гороху (Баллтрап, НС Мороз). Мета досліджень – визначити кращий сорт гороху та дозу припосівного добрива. Найвищий рівень чистого доходу 24481,8 грн./га, отримали при вирощуванні сорго сорту НС Мороз у варіанті з припосівною дозою амофосу 44кг/га. Даний агрозахід рекомендується виробництву. In this final qualification work, the effect of two multiple doses of ammophos when used as a seeding fertilizer in the cultivation of four varieties of spring (Salamanka, Madonna) and winter peas (Balltrap, NS Moroz) was studied. The purpose of the research is to determine the best pea variety and the dose of seeding fertilizer. The highest level of net income of 24481.8 UAH/ha was obtained when growing sorghum of the NS Moroz variety in the variant with a seeding dose of ammophos of 44 kg/ha. This agricultural measure is recommended for production.
The influence of mineral fertilizers on the productivity of winter and spring peas in the Steppe of Ukraine
Keywords: горох озимий; горох ярий; сорт; winter peas; spring peas; variety